2016
DOI: 10.1063/1.4954994
|View full text |Cite
|
Sign up to set email alerts
|

On the electron drift velocity in plasma devices with E×B drift

Abstract: The structure and various components of the electron drift velocity are discussed in application to plasma discharges with the E×B drift. In high density plasmas, the contribution of the diamagnetic drift can be of the same order magnitude as the E×B drift. It is pointed out that curvature and gradient drifts associated with magnetic field inhomogeneities manifest themselves via the electron pressure anisotropy. Estimates show that the components of the diamagnetic drift related to the electron pressure anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Chapurin and Smolyakov [40] showed that the full expression for the fluid (averaged) drift can be written as the sum of the E × B drift, diamagnetic drift, and pressure anisotropy drift. We shall refer to this velocity as v net .…”
Section: Temporal Variation Of Electron Properties: Arcondition 1 (Pe...mentioning
confidence: 99%
“…Chapurin and Smolyakov [40] showed that the full expression for the fluid (averaged) drift can be written as the sum of the E × B drift, diamagnetic drift, and pressure anisotropy drift. We shall refer to this velocity as v net .…”
Section: Temporal Variation Of Electron Properties: Arcondition 1 (Pe...mentioning
confidence: 99%
“…The fact that the measured drift is of nearly the same magnitude regardless of the magnetic field direction suggests that the   É B drift dominates the diamagnetic and curvature drifts near the exit plane. This observation might differ at distances further downstream [69]. The maximum electron drift velocity can be used to estimate the maximum electric field in the acceleration region of the thruster.…”
Section: Magnetic Field Directionmentioning
confidence: 99%
“…Consistent with the gyrokinetic modelling, the field's magnitude, B, decreases over the major radius of the torus (B ∝ 1/R), and κ = − R/R. Curvature drifts are encoded via diamagnetism in this fluid representation [65] with the curvature operator, (17) but with an unperturbed field vector distinguishing it from electromagnetic theory. The constant coefficients κ s and η s correspond to parallel thermal conductivity and electrical resistivity, respectively.…”
Section: Machine Learning Fluid Theorymentioning
confidence: 67%